2022
DOI: 10.1186/s40634-022-00507-6
|View full text |Cite
|
Sign up to set email alerts
|

Anterior cruciate ligament microfatigue damage detected by collagen autofluorescence in situ

Abstract: Purpose Certain types of repetitive sub-maximal knee loading cause microfatigue damage in the human anterior cruciate ligament (ACL) that can accumulate to produce macroscopic tissue failure. However, monitoring the progression of that ACL microfatigue damage as a function of loading cycles has not been reported. To explore the fatigue process, a confocal laser endomicroscope (CLEM) was employed to capture sub-micron resolution fluorescence images of the tissue in situ. The goal of this study w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 39 publications
2
16
0
Order By: Relevance
“…Thus, to mitigate ACL overuse injuries, we need a greater understanding of how the collagen physiologically, structurally, and functionally responds to repetitive submaximal loading during adolescence. Here, we showed that in vivo submaximal fatigue loading of the ACL in mice reproduces a similar damage signature to that reported in human cadaveric and patient ACLs, 4,8 and by many other research groups across musculoskeletal tissues. 26,28,29,33 Notably, in vivo submaximal fatigue loading generates molecular collagen damage within the ACL, which results in diminished mechanical properties with continued repetitive loading.…”
Section: Discussionsupporting
confidence: 82%
“…Thus, to mitigate ACL overuse injuries, we need a greater understanding of how the collagen physiologically, structurally, and functionally responds to repetitive submaximal loading during adolescence. Here, we showed that in vivo submaximal fatigue loading of the ACL in mice reproduces a similar damage signature to that reported in human cadaveric and patient ACLs, 4,8 and by many other research groups across musculoskeletal tissues. 26,28,29,33 Notably, in vivo submaximal fatigue loading generates molecular collagen damage within the ACL, which results in diminished mechanical properties with continued repetitive loading.…”
Section: Discussionsupporting
confidence: 82%
“…The exact combination of recovery time, reduced or modified loading, and nutrition that is needed to decrease the potential for sustaining an overuse noncontact ACL injury is not currently known. 8,16 Taken in the aggregate, however, any combination of increased or enhanced recovery, reduced or modified loading, and improved nutrition has high potential to prevent fatigue failure from overuse-related noncontact ACL injury mechanisms. 16 Let's start these discussions.…”
mentioning
confidence: 99%
“…Within this scenario, focused attention solely on high volume skill or performance training and competition may get the better of the capacity of the ACL ECM to heal, replacing natural recovery homeostasis with progressive collagen fiber and crosslink degradation, leading to the ligament histopathology that precedes sudden noncontact fatigue rupture. 8,24 For any athlete who has ever experienced this, it remains a memorable event for the rest of their life and often is later recalled as the initial marker that led to the need for more knee surgery.…”
mentioning
confidence: 99%
See 2 more Smart Citations